Splatoon 3. Splatlands, Volume 5 - Hinodeya, Sankichi (Splatoon 3, 2025)
"After falling asleep on the train to Inkopolis Square, Goggles wakes up in a city drained of color! Now it's up to him and his friends to unravel the mysteries of this new world, including the ominous-looking Spire of Order. What awaits them inside?!" --